STRATEGI FRONTLINER DALAM MENANGAN KELUHAN MASYARAKAT UNTUK MENINGKATKAN KUALITAS PELAYANAN PUBLIK (STUDI KASUS DI KANTOR KECAMATAN MEDAN TIMUR) - Lewi Syahputra Marpaung; Jonson Rajagukguk; Kepler Sinaga (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to determine the strategies used by frontliners in handling public complaints and how these strategies contribute to improving the quality of public services at the Medan Timur District Office. Quality public service is an important indicator in the implementation of government administration, especially at the district level which directly interacts with the community. In the administrative service process, public complaints often arise due to a lack of understanding of service procedures, delays in document processing, and limitations in service facilities. Therefore, the role of frontliners as officers who directly interact with the community becomes very important in handling these complaints. This research uses a qualitative research method with a case study approach. Data collection techniques were carried out through interviews, observations, and documentation involving informants consisting of frontliner officers and members of the public who received services at the Medan Timur District Office. Data analysis was conducted using the Miles and Huberman interactive analysis model which includes data reduction, data display, and conclusion drawing. The results of the study show that the strategies used by frontliners in handling public complaints include receiving and listening to complaints directly, providing explanations regarding service procedures, checking the completeness of required documents, and coordinating with supervisors when problems cannot be resolved directly. These strategies help the public better understand the service procedures and create good communication between service officers and the community. Therefore, the complaint handling strategies implemented by frontliners play an important role in improving the quality of public services at the Medan Timur District Office.